FACTORS OF INFLUENCE ON LEGAL PROFESSION IN THE CONDITIONS OF THE MODERN INFORMATION SPACE - Сопілко, Ірина Миколаївна; Череватюк, Вікторія Богданівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Object: summing up the results of the IX International scientific and practical conference «Jurisprudence in the modern information space», to analyze the factors of influence on the future of the legal profession and to reveal the role of an university in the preparation of a competent and competitive lawyer capable of meeting the requirements and needs of society in a modern information space. Methods: general and specific scientific (special) methods were used to achieve the research goal. The use of these methods made it possible to analyze the factors of influence on the future of the legal profession. Results: work on the formation of a system of legal education and science, of course, should occur through consolidated efforts of both the academic community and employers, the labor market, state authorities - all those who are in one way or another involved in solving this issue. The further development of legal science and education is directly related to the need to solve the practical problems faced by society and the state in the current conditions of the information space, improvement of legislation, activation of research aimed at solving specific problems in various branches of law, which are associated with the peculiarities of the digital age. Discussion: the authors offer to improve the training process, plans and programs in accordance with international educational standards. As for legal science, it is worth moving from increasing of quantitative indicators in the assessment of scientific achievements, to new models and technologies for creation and distribution of journals; scientometric tools for evaluating scientific research; digital support for scientific achievements as well as the creation and use of scientific electronic resources.